Analysis of extracellular vesicle miRNA profiles in heart failure. Issue 13 (2nd June 2020) - Oh, Jae Gyun; Lee, Philyoung; Gordon, Ronald E.; Sahoo, Susmita; Kho, Changwon; Jeong, Dongtak
Abstract: Extracellular vesicles (EVs) have recently emerged as an important carrier for various genetic materials including microRNAs (miRs). Growing evidences suggested that several miRs transported by EVs were particularly involved in modulating cardiac function. However, it has remained unclear what miRs are enriched in EVs and play an important role in the pathological condition. Therefore, we established the miR expression profiles in EVs from murine normal and failing hearts and consecutively identified substantially altered miRs. In addition, we have performed bioinformatics approach to predict potential cardiac outcomes through the identification of miR targets. Conclusively, we observed approximately 63% of predicted targets were validated with previous reports. Notably, the predicted targets by this approach were often involved in both beneficial and malicious signalling pathways, which may reflect heterogeneous cellular origins of EVs in tissues. Lastly, there has been an active debate on U6 whether it is a proper control. Through further analysis of EV miR profiles, miR‐676 was identified as a superior reference control due to its consistent and abundant expressions. In summary, our results contribute to identifying specific EV miRs for the potential therapeutic targets in heart failure and suggest that miR‐676 as a new reference control for the EV miR studies.